Peningkatan Pemahaman Dasar Pola Makan Sehat guna Penanggulangan Stunting di Desa Kebonharjo, Kecamatan Polanharjo, Kabupaten Klaten - Wahyu Dwi Saputra; Aulia Maharraning Mustikawati; Devani Adinda Putri (Direktorat Pengabdian kepada Masyarakat, 2024)
Nutritional problems with chronic conditions caused by certain situations, one of which is an unhealthy diet, is one of the factors that cause stunting. Referring to the Indonesian Nutrition Status (INS) data for 2022 and 2021, stunting in Klaten Regency is at 18.2% in 2022, a significant increase from 2021, which was recorded at 15.8%. Based on this, a socialisation activity with the title